Towards a Unified Arabic Government Services Chatbot Based on Ontology - Areed, Sufyan (2020)
The amount of information has risen considerably since the beginning of the electronic era. Meanwhile, the relationships between various types of information have become more and more complex. On the other hand, the growing number of users have encouraged researchers to take an advantage of this information and develop techniques which analyze the experiences of customers to accommodate their requirements and satisfy their needs. Since the birth of the term "e-government", the amount of structured and unstructured information has increased dramatically, which has forced all government entities worldwide to provide many call centers with long working hours that may reach to 24/7 in some entities to answer users' questions related government services, regardless of the time wasted by the clients while waiting to get in touch with the agent. In fact, UAE government is not an exception. As far as Dubai government is concerned, some entities have taken a step forward by introducing their own chatbot technology to respond to customer inquiries. However, the challenges fraught with the chatbot development in general in addition to the challenges associated with the Arabic language in particular, made it extremely difficult to design a unified chatbot that is capable to respond to all services provided by Dubai government especially when dealing with the Arabic language. In this study, a novel approach is proposed to extract an Arabic language knowledge base from a previously built ontology for more than 500 services provided by the Dubai government in order to use the extracted knowledge base into a chatbot application through Artificial Intelligence Markup Language (AIML) files. The current ontology is an enhancement which builds on a previously created ontology. Furthermore, a chatbot response algorithm is proposed to respond to government services queries through a hybrid of three different approaches that were executed in a pipeline fashion based on the query complexity. The feasibility of the proposed algorithm has been proven through executing multiple experimental tests for the same set of questions (414 questions) that were performed on the ontology earlier, then it has been compared with the ontology itself and the formal chatbot that has been designed by Smart Dubai Government (Rashid) chatbot. High Accuracy score has been achieved by the proposed algorithm that reached 96% with Recall of 100% and Precision of 96% as well. These results confirmed that the performance of the proposed algorithm could outperform both a previously developed chatbot-based on ontology and Rashid chatbot as well.